Anti-vascular endothelial growth factor indications in ocular disease - Cornel, Stefan (Rom J Ophthalmol, 2015)
The purpose of this systemic review was to investigate the indications of anti-vascular endothelial growth factor (anti-VEGF) in the treatment of ocular diseases. For this, a comprehensive literature research was performed exploring the current use of anti-VEGF in a variety of retinal or anterior segment diseases and highlighting the visual outcome for these patients. The anti-VEGF therapy is now commonly used for a wide range of pathologies like age-related macular degeneration, retinal vein occlusion or diabetic retinopathy. Pathological processes such as abnormal neovascularization, ocular angiogenesis and macular edema which can greatly reduce visual acuity are now targeted by anti-VEGF treatment, having a major impact on vision.